S108 Low skeletal muscle strength and physical activity are associated with poor outcomes in pulmonary arterial hypertension. (15th November 2016) - Garfield, BE; Shao, D; Parfitt, L; Harries, C; Price, L; Dimopoulos, K; Polkey, MI; Kemp, P; Wort, SJ
Abstract : Introduction: Skeletal muscle wasting and low physical activity are emerging as important potentially modifiable complications of pulmonary arterial hypertension (PAH). In other conditions, such as COPD and heart failure, low muscle strength and low levels of activity have been shown to be associated with poor outcomes. We aimed to define the association of muscle strength and physical activity with hospital admission rates, long term quality of life and mortality in patients with PAH. Methods: Twenty-eight patients with PAH had their quadriceps maximal volitional capacity (QMVC), step count, BNP and 6MWD measured. At least 1 year later, these patients' records were reviewed and data were collected on mortality, transplantation, admission to hospital and quality of life using the EMPHASIS 10 questionnaire. QMVC was normalised to BMI and 24 patients with valid step count data were included in the analysis of activity. Kaplan-Meier plots were constructed to define mortality and ROC analysis was used to demonstrate which factors most closely predicted hospital admission. Pearson correlation was used to define the associations with follow-up quality of life. Results: Kaplan–Meier plots demonstrated that patients with a QMVC/BMI < 1.1 and those with a step count < 2500 per day were significantly more likely to die or undergo transplant than those above these cut-offs (Figure 1 A and B ). ROC analysis showed that a QMVC/BMI <1.5 predicted hospital admission over the follow up period with a sensitivity of 93% and a specificity of 62%. It also demonstrated that QMVC was superior to the 6MWD in predicting hospital admission (AUC 0.83, p = 0.003 vs. AUC 0.73, p = 0.017). Finally QMVC/BMI was significantly correlated to quality of life at follow-up in this cohort (Pearson r = −0.47, p = 0.018). Discussion: Our data suggests that, like in other chronic conditions, low muscle strength and low physical activity in PAH are associated with poor outcomes. Treatment strategies targeting the muscle and physical activity levels may improve outcomes in terms of both quality of life and mortality.